2015
DOI: 10.1093/annonc/mdv077
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of interim PET–CT-guided response-adapted therapy in advanced Hodgkin's lymphoma

Abstract: CTRI/2012/06/002741 (http://www.ctri.nic.in) and NCT01304849 (http://www.clinicaltrials.gov).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…There was high risk of bias in the domain of patient selection in 7 studies [8][9][10][11][12][13][14], because these studies did not systematically perform biopsies in all patients with FDG-avid lesions but in only a sample of these cases. There was unknown risk of bias in the domain of the index test in 6 studies [11,[13][14][15][16][17], because these studies did not report whether the interpreters of the FDG-PET scans where blinded to the biopsy results. There was unknown risk of bias in the domain of the reference test in all 11 studies [8][9][10][11][12][13][14][15][16][17][18], because these studies did not report whether the interpreters of the biopsies were blinded to the FDG-PET scans.…”
Section: Methodological Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…There was high risk of bias in the domain of patient selection in 7 studies [8][9][10][11][12][13][14], because these studies did not systematically perform biopsies in all patients with FDG-avid lesions but in only a sample of these cases. There was unknown risk of bias in the domain of the index test in 6 studies [11,[13][14][15][16][17], because these studies did not report whether the interpreters of the FDG-PET scans where blinded to the biopsy results. There was unknown risk of bias in the domain of the reference test in all 11 studies [8][9][10][11][12][13][14][15][16][17][18], because these studies did not report whether the interpreters of the biopsies were blinded to the FDG-PET scans.…”
Section: Methodological Quality Assessmentmentioning
confidence: 99%
“…There was unknown risk of bias in the domain of the index test in 6 studies [11,[13][14][15][16][17], because these studies did not report whether the interpreters of the FDG-PET scans where blinded to the biopsy results. There was unknown risk of bias in the domain of the reference test in all 11 studies [8][9][10][11][12][13][14][15][16][17][18], because these studies did not report whether the interpreters of the biopsies were blinded to the FDG-PET scans. There was unknown risk of bias in the domain of flow and timing…”
Section: Methodological Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the heterogeneous results on the predictive value of positive interim FDG‐PET findings in advanced‐stage Hodgkin lymphoma underline that the claim by some investigators that persistence of disease at FDG‐PET confers a dismal prognosis has not convincingly been proven. Non‐randomised trials (Table ) in which all interim FDG‐PET‐positive patients are allocated to intensified therapies should be avoided; a gain in PFS following intensified treatment compared to historical data (particularly those studies reporting a dismal prognosis in FDG‐PET‐positive patients) following continuation of standard therapy does not suffice. Only randomised trials will provide more insight into the gain in PFS and OS following upfront interim FDG‐PET‐based treatment escalation in advanced‐stage Hodgkin lymphoma.…”
Section: Predictive Value Of Interim Fdg‐pet Following Continuation Omentioning
confidence: 99%
“…At a median follow-up of 24 months (4-74), PFS was 82 % for the entire cohort of advanced-stage patients. Two very small prospective, single-centre phase II clinical trials have been recently concluded and published, adopting a escalation a de-escalation strategy based on interim PET result after 2 courses of ABVD or BEACOPP, respectively [82,83]. While data from Ganesan [80] seem very similar to that reported in the interim analysis of S0812, RATHL and HD 0607 [76][77][78], Deau et al reported the results of a retrospective analysis on a small cohort of 64 advanced-stage HL who were consecutively enrolled in a single institution in a time lag spanning over 6 years.…”
Section: Pet Response-adapted Clinical Trials Starting With Beacoppmentioning
confidence: 99%